2015
DOI: 10.1136/heartjnl-2014-307276
|View full text |Cite
|
Sign up to set email alerts
|

Potential underdiagnosis of obstructive sleep apnoea in the cardiology outpatient setting

Abstract: Despite significant scientific evidence pointing to OSA as an emerging cardiovascular risk factor, OSA is still underdiagnosed in several cardiology subspecialties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
59
0
6

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 108 publications
(68 citation statements)
references
References 23 publications
2
59
0
6
Order By: Relevance
“…It is investigated by sleep specialists, respiratory physicians and otorhinolaryngologists. Cardiologists disregard OSA in their clinical reasoning, as Costa et al 7 show in their Heart paper. Studying a representative sample of various cardiological subspecialties in a tertiary care university-affiliated hospital in São Paulo, Brazil, they identified that among 500 consecutive patients evaluated, 258 patients (51.6%) had a high risk for OSA by the Berlin questionnaire.…”
mentioning
confidence: 99%
“…It is investigated by sleep specialists, respiratory physicians and otorhinolaryngologists. Cardiologists disregard OSA in their clinical reasoning, as Costa et al 7 show in their Heart paper. Studying a representative sample of various cardiological subspecialties in a tertiary care university-affiliated hospital in São Paulo, Brazil, they identified that among 500 consecutive patients evaluated, 258 patients (51.6%) had a high risk for OSA by the Berlin questionnaire.…”
mentioning
confidence: 99%
“…Although they studied a larger number of patients, prevalence rates of both OSA and cancer were obtained retrospectively from a health database. Therefore, the presence of OSA could be underestimated, since it is a frequently underdiagnosed condition [19].…”
Section: Discussionmentioning
confidence: 99%
“…1 However, OSA remains largely underrecognized in this group of patients in clinical practice. 1 Why is that?…”
mentioning
confidence: 99%
“…1 However, OSA remains largely underrecognized in this group of patients in clinical practice. 1 Why is that? One possible explanation is that many nonsleep specialists are not familiarized with OSA diagnosis and treatment.…”
mentioning
confidence: 99%